The effect of the use of the papoose board on the behavior and attitudes of the pediatric dental patient - Galvez, Bernard Q.A.; Recto, Ma. Cristina A.; Dimanlig, Anna Maria C. (Adviser).
A survey was performed by administering questionnaires to dentists and parents of pediatric dental patients upon whom the papoose board was used. The study was conducted in Pediatric Dental Center (PDC), Philippine Children Medical Center (PCMC), and University of the Philippines College of Dentistry (UPCD). This survey was designed to determine the effect of the use of the papoose board on the behavior of the child on the next appointment. Data was obtained from twenty dentists and parents. According to this study, there was an improved or no change in behavior among the children after the papoose board was used on them. There was an improvement of 35% in the willingness of the child to go to the dentist, while 60% exhibited no change. 80% gave a positive attitude towards the dentist and 75% had a decrease fear and anxiety level after the papoose board was used. 65% had an improved behavior during dental treatment as perceived by the dentist. While 55% of the parents thought that their child was more behaved and only 5% thought otherwise. 60% of the children remembered the papoose board being used on them and 60% thought that the papoose board was used because they were "bad." The significant difference between the 3 institutions was, whether the child remembered the papoose board being used on him. From this study, it can be concluded that the use of the papoose board did not have a negative effect on the behavior of the child.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.